Climate Change and Crop Yields in Iran and Other OIC Countries - Seyed Hossein Mirjalili; Mahdis Motaghian Fard (International Journal of Business and Development Studies, 2019)
Climate change is the main phenomenon that directly affects the world environment, and changes in the environment affect economic sectors differently. The most important impacts of climate change would be on enhancing the average global temperature and the decrease in precipitation. The agricultural sector is the first and most affected sector in the climate change. We examined the impact of temperature and precipitation variables on the agricultural yield for three common products namely fruits, rice and corn in 14 OIC countries including Iran. The share of employment in the agricultural sector as compared to the total employed is a control variable. By estimating the model using the panel data method over the years 1992 and 2015, the results indicate a negative effect of temperature on the agricultural sector. Precipitation has a positive effect and the share of employment in agriculture has a negative effect.
Keywords: Q54; Q15; E23; O13; 630; Climate change; Agricultural productivity; OIC countries; Temperature; Precipitation; Employment